2020
DOI: 10.33594/000000275
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Prolidase Induces Autophagic Death in MCF-7 Breast Cancer Cells

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The procedure of Western-immunoblot analysis was described previously (Zareba et al 2017(Zareba et al , 2020. Protein concentration was measured by the method of Lowry et al (Lowry et al 1951) Cell lysates were subjected to SDS-PAGE in 10% polyacrylamide gel electrophoresis.…”
Section: Western-immunoblot Analysismentioning
confidence: 99%
“…The procedure of Western-immunoblot analysis was described previously (Zareba et al 2017(Zareba et al , 2020. Protein concentration was measured by the method of Lowry et al (Lowry et al 1951) Cell lysates were subjected to SDS-PAGE in 10% polyacrylamide gel electrophoresis.…”
Section: Western-immunoblot Analysismentioning
confidence: 99%
“…It seems that in the mechanism of PRODH/POX-induced apoptosis or survival, proline availability and PRODH/POX expression are equally important. Previously, we have found correlation between PRODH/POX and prolidase in MCF-7 cells (Zareba et al 2020 , 2017 ). PRODH/POX silencing contributed to drastic increase in prolidase activity, while overexpression of prolidase attenuated PRODH/POX expression contributing in both conditions to pro-survival phenotype of the cells.…”
Section: Introductionmentioning
confidence: 75%
“…PRODH/POX expression is often down-regulated in various tumors, limiting mitochondrial proline degradation and PRODH/POX-dependent apoptosis and autophagy. Some studies suggested that critical factor for the process is proline availability that depends on the activity of prolidase (enzyme supporting cytoplasmic proline level) and the rate of proline utilization in process of collagen biosynthesis (Zareba et al 2020 , 2017 ; Zareba and Palka 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of response element for p53 protein in the promoter sequence of the gene coding PRODH/POX has been demonstrated. It shows direct participation of p53 in the transcription of PRODH/POX [11]. However, in MDA-MB-231 cells it has probably low importance due to mutation [52,53] that eliminate the transcription factor as a player in the mechanism driving PRODH/POXdependent apoptosis in ER negative breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, when electrons are transferred directly to oxygen then the reactive oxygen species (ROS) are formed inducing apoptosis or autophagy [7][8][9]. Although the mechanism for switching from ATP to ROS production is not known, several factors have been implicated in this process [10,11]. One of them is prolidase, the enzyme supporting substrate for PRODH/POX.…”
Section: Introductionmentioning
confidence: 99%